2014
DOI: 10.1002/2013gl059004
|View full text |Cite
|
Sign up to set email alerts
|

Global interior eddy available potential energy diagnosed from Argo floats

Abstract: By combining all Argo profiles for the period 2002 to present, a cumulative density function is constructed on a 3-D grid of the global ocean. This function quantifies the statistics of isopycnals: time-averaged density, root-mean square of isopycnal displacement, and eddy available potential energy (EAPE). EAPE is the analogue of the eddy kinetic energy, but for the potential energy reservoir. Because it is essentially tied to the spatial structure and magnitude of mesoscale activity, EAPE is an important qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 17 publications
3
58
0
Order By: Relevance
“…Compared to EKE, it shows a more significant increase downstream of the Charleston Bump, and it peaks at the upon-separation region. The resemblance of the horizontal structure between EPE and EKE was also found in the global EPE map constructed from the Argo profiles by Roullet et al (2014). For the entire GS domain, the EPE reservoir is 71.48 PJ, which is smaller than the EKE reservoir.…”
Section: Summary and Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Compared to EKE, it shows a more significant increase downstream of the Charleston Bump, and it peaks at the upon-separation region. The resemblance of the horizontal structure between EPE and EKE was also found in the global EPE map constructed from the Argo profiles by Roullet et al (2014). For the entire GS domain, the EPE reservoir is 71.48 PJ, which is smaller than the EKE reservoir.…”
Section: Summary and Discussionmentioning
confidence: 62%
“…4c). Roullet et al (2014) recently derived a 3D global EPE map from the Argo profiles and showed that the horizontal structure of the subsurface EPE is very close to that of the surface EKE for the global ocean.…”
Section: Energy Reservoirsmentioning
confidence: 99%
“…Comparison with Roullet's (2014) fluctuating APE estimate Figure 6 shows the distribution of fluctuating APE density at the surface and at 250-, 500-, and 1000-m depths [the same depths used in Fig. 2 of Roullet (2014)].…”
Section: Resultsmentioning
confidence: 99%
“…Depths, at which eddies seem responsible for the biggest part of local EKE, can actually vary with the latitude. An independent benchmark of the ocean interior turbulence has been recently provided by Roullet et al (2014) from the analysis of the Argo density profile down to 2000 m. They evaluate the eddy available potential nnergy (EAPE) generated by the anomalous vertical isopycnal displacements with respect to the stationary, long-term value at different depths. In particular, the interior maxima of EAPE extracted by Argo floats in several ocean areas, suggest the presence of local energy source at depths.…”
Section: Reke Vertical Profilesmentioning
confidence: 99%